Conservative Approach in the Management of Radicular Cyst in a Child: Case Report - Narendra Varma Penumatsa; Srinivas Nallanchakrava; Radhika Muppa; Arthi Dandempally; Priyanaka Panthula (Case Reports in Dentistry)
Radicular cyst is the most common odontogenic cystic lesion of inflammatory origin. It is also known as periapical cyst, apical periodontal cyst, root end cyst, or dental cyst. It arises from epithelial residues in the periodontal ligament as a result of inflammation. The inflammation usually follows the death of dental pulp. This paper presents a case report of a patient with radicular cyst associated with a primary molar.